Changes in Doctoral Education Worldwide - Nerad, Maresi (My University, 2008)
Maresi Nerad will present a synthesis of her forthcoming book, Toward a Global PhD? Forces and Forms in Doctoral Education Worldwide (University of Washington Press, April 2008), and her ongoing research on this topic. In comparing trends in 14 countries, Nerad has identified the emergence of a truly global system of doctoral education. This common model retains contribution to knowledge as central in defining the doctorate and seeks in a variety of ways to link doctoral education more closely to contemporary societal and economic needs. The commonalities emerging show that doctoral education in most countries is responsive to market demands and commoditization of doctoral degrees, and that there is a global need to confront new problems with new ways of doing research. Nerad will also discuss the development of a conceptual framework for understanding doctoral education within globalization. This presentation is part of the Ideas and Universities International Video Seminar Series. The program theme for the spring 2008 semester is "Universities as Organizations: Looking Inwards, Looking Outwards."
Keywords: Teaching and Learning; International and Comparative